TRADE UNION ORGANIZATIONS DURING THE PERIOD OF RESTORING THE KARAKALPAK STATEHOOD - Kudyarova Tillakhan Asanovna (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The article contains archival sources on the history of the trade union organization of Karakalpakstan. Based on the analysis of historiographic material on the history of the trade union organization, the stages of formation and formation and role in public relations during the period of Soviet totalitarianism were studied. And also, the essence and nature, internal connections and problems of the functioning of the trade unions of Karakalpakstan in the conditions of the command-administrative system were analyzed.